Quantitative Evaluation of Zigbee Localization Based on Weighted Centroid with Quadratic Means - Thammavong, Lonesy; Khongsomboon, Khamphong; Promwong, Sathaporn (My University, 2018)
Wireless localization for indoor radio wave propagation channels are significant interested research topic. The indoor localization is widely applying in wireless sensor network. Weighted centroid algorithm is one of the algorithm that able to work in range-free scenario of indoor localization. This research proposed the modified of weighted centroid algorithm with quadratic mean based on received signal strength of the frequency at 2.4 GHz. The ZigBee is a promising technology for operate at 2.4 GHz and good performance in the indoor environment. The experimental results are show as the average received signal strength value, the distance error, and the comparison of commutative distribution function of distance error between the normal weighted centroid algorithm and the modify weighted centroid algorithm at 1 m. The precision of modify weighted centroid algorithm is better than the weighted centroid algorithm more than 9% and have 17% no error position estimation.
Keywords: improve weighted centroid algorithm; indoor wireless localization; quadratic means; received signal strength; ZigBee